Pencegahan Fraud Melalui Budaya Organisasi, Good Corporate Governance Dan Pengendalian Internal - Rustandy, Teddy; Sukmadilaga, Citra; Irawady, Cahya (JPAK : Jurnal Pendidikan Akuntansi dan Keuangan, 2020)
PT Pos Indonesia (Persero) is one of the state-owned enterprises that has experienced various cases of fraud. The fraud cases that occurred in these companies have caused significant financial losses to the company and of course the state's financial losses. PT Pos Indonesia (Persero) has large assets, with more than 4,000 offices scattered throughout the archipelago. Therefore, preventive measures are needed in order to protect their assets from fraud. The method used in this research is a case study method with a quantitative descriptive approach. The data analysis technique used is the path analysis method. As for the research population, 11 regional post offices and 205 inspection post offices (Kprk) throughout Indonesia, so that the total population is 216 offices. While the sample method used in this study is the saturated sampling method (census), in which all members of the population are determined to be the research sample. The results showed that organizational culture, good corporate governance and internal control simultaneously and partially had a significant and positive influence on fraud prevention at PT Pos Indonesia (Persero). This means that the better the implementation of organizational culture, good corporate governance and internal control, the higher the level of fraud prevention at PT Pos Indonesia (Persero).